Current Management Guidelines on Hyperlipidemia: The Silent Killer. (6th August 2021) - Su, Lilly; Mittal, Rea; Ramgobin, Devyani; Jain, Rahul; Jain, Rohit
Abstract : Given the high incidence of cardiovascular events in the United States, strict control of modifiable risk factors is important. Pharmacotherapy is helpful in maintaining control of modifiable risk factors such as elevated lipids or hypercholesterolemia. Hypercholesterolemia can lead to atherosclerotic disease which may increase the risk of acute coronary events. Statin therapy has long been a mainstay in the treatment of hypercholesterolemia, but while highly regarded, statin therapy also has side effects that may lead to patient noncompliance. Therefore, various medicines are being developed to manage hypercholesterolemia. This paper will discuss the role that lipids play in the pathophysiology of atherosclerotic disease, review the current lipid management guidelines, and discuss new treatment options that are alternatives to statin therapy.